Hyperphosphorylated tau in young and middle-aged subjects - Elobeid, Adila; Soininen, Hilkka; Alafuzoff, Irina (Acta neuropathologica, 2012)
The brain tissue obtained from ninety-five cognitively unimpaired subjects, with ages ranging from 22 to 50 years upon death, were immunohistochemically assessed for neurodegenerative changes, i.e., hyperphosphorylated tau (HPτ) and β-amyloid (Aβ) pathology in predilection neuroanatomical areas. HPτ pathology was observed in the transentorhinal cortex and/or the locus coeruleus (LC) in 33% of the subjects, without any obvious risk factors known to alter the microtubule-associated protein. HPτ pathology was noted in the LC in 25 out of 83 subjects (30%), lacking concomitant cortical Aβ or transentorhinal HPτ pathology. This observation was present even when assessing only one routine section of 7 μm thickness. The recent suggestion of prion-like propagation of neurodegeneration and the finding of neurodegeneration being quite common in middle-aged persons is alarming. It is noteworthy, however, that a substantial number of neurologically unimpaired subjects even at a very old age display only sparse to modest extent of neurodegenerative pathology. Thus, only a subset of subjects with neurodegenerative changes early in life seem to progress to a symptomatic disease with ageing. This observation brings forth the notion that other, yet unknown modifying factors influence the progression of degeneration that leads to a symptomatic disorder. The known association between alterations in the LC and mood disorders, and the finding of the LC being frequently affected with HPτ pathology suggest that clinicopathological studies on young subjects both with or without mood disorders are warranted.